The Implementation of Thematic Method in Aqidah Akhlak Learning - Nila Nahdiyana; Jauharotul Makniyah; Luthfatul Qibtiyah (Saniya Institute, 2025)
This study explores the application of the thematic method in Aqidah Akhlak for Grade V students at Madrasah Ibtidaiyah and identifies the supporting and hindering factors that influence its effectiveness. Using a qualitative approach through interviews, observations, and documentation, the research reveals that thematic learning enables students to engage more actively in the learning process. The method provides opportunities for students to connect religious values with real-life experiences through discussions, critical thinking, and hands-on activities. The findings indicate that supporting factors include a conducive learning environment, adequate learning resources, and relevant curriculum design. On the other hand, obstacles such as limited teacher understanding of thematic planning and students’ perception of excessive assignments remain challenges. Despite these constraints, the thematic approach proves effective in enhancing students’ learning motivation and character development. This study suggests that ongoing teacher training and collaborative learning strategies are essential to improve the implementation of thematic learning in Islamic education settings. The findings imply that effective thematic learning in Aqidah Akhlak requires well-prepared teachers and supportive learning environments.